Perbandingan Eksistensi Media Arus Utama Televisi Dan Media Sosial Sebagai Sumber Berita Terpercaya Di Jabodetabek - Ketrin My Rebeka Samosir (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Media continues to develop, with the support of the internet media has given birth to new networks, namely social media. The emergence of the internet is a phenomenon that has an influence on human life. Every media competes to remain in existence and in demand by the public. Various information is disseminated to all media users for the development of communication and information science. The aim of this research is to explore how the existence of mainstream media and social media compare as trusted news sources for the people of Jabodetabek. The research method used is a descriptive qualitative research method with semi-structured interview data collection techniques. The theory used is audience reception theory to find out how messages are received by media users. The research results from comparing the existence of mainstream media and social media as trusted news sources are divided into two, namely existence in terms of users and in terms of trust. From a user perspective, social media is the most popular media. Meanwhile, in terms of trust, social media and mainstream media are equally trusted. However, there is something that must be considered, users' trust in social media is determined by accounts that contain news.